G516(P) How do neonatal units support siblings following loss? – a national survey. (24th May 2017) - Henderson, R; Minchella, S; Vasudevan, C
Abstract : Background: Supporting siblings following loss of an infant is increasingly recognised as an important aspect of neonatal bereavement support. The grief process in children is often complicated by feelings of loss, guilt as well insecurity about their parental wellbeing. There are some existing recommendations from both the Royal College of Paediatrics and Child Health and the British Association of Perinatal Medicine on the various aspects of family support but there is great variation in practice when it comes to supporting siblings following loss of a neonate. Aims/objectives: The aim of this study was to explore the practices across all the Neonatal Intensive Care Units (NICUs) in England focussing on sibling support following neonatal loss. We studied the interventions, support systems and resources available for bereaved siblings within the neonatal service. Methodology: We conducted a structured telephonic survey of all the 44 NICUs in England. A proforma was used and specific questions were asked from bereavement nurse within each neonatal service regarding resources, availability of multidisciplinary teams and written information on sibling support following neonatal loss. This study was completed over a period of 6 weeks between May and June 2016. The data was collected by the research team and analysed descriptively. Results: Results from 39 out of the 44 NICUs. 34% of the units provide support for siblings after neonatal death. This was provided by a combination of counsellors, psychologists/family support nurse within the neonatal team. 60% involved external services including hospice or a charity organisation to provide long term support. Only 50% of units had any written materials or resources focussed on sibling support. 10% of the NICUs did not have an identified bereavement support/end of life care team. Conclusion: This study identifies significant variation in practice across the NICUs in the country in terms of supporting siblings following neonatal death. It reiterates the need for a much more unified approach and sharing resources/good practice models across the different units. Sibling support should be an integral component of the bereavement support offered by neonatal services.